ANALISIS KOHESI ANAFORA DAN KATAFORA PADA TAJUK RENCANA KORAN KOMPAS - Endang Wiyanti; Yulian Dinihari (BAHASTRA, 2017)
The purpose of this study was to determine the cohesion aspect anaphora and katafora the Kompas newspaper editorials. The method used in this study is qualitative content analysis with technical analysis is a method used to examine in greater depth discourse. The results showed that of the 12 editorial discourse data showed as many as 164 pairs of sentences. Research data of 164 couples found 67 sentences have cohesion anaphora or as much as 40,48% and only 14 pairs sentence with katafora cohesion or 8,54%. Aspects of cohesion anaphora is used predominantly in building cohesion sentence. From the use of markers, can be show that demonstrative pronouns as much as 54,32% more often appear in a sentence with cohesion. It indicates that the demonstrative pronoun marker has an important role in forming the sentence cohesion.